Perencanaan Sumur Resapan Sebagai Upaya Pengelolaan Air Larian di Perumahan Teduh Katapang - Farid, Ahmad; Eka Wardhani (Jurnal Serambi Engineering, 2025)
Teduh Katapang Residence in Bandung Regency was built on agricultural land, resulting in a reduction of the water catchment area. Runoff water management in Teduh Katapang Housing is a challenge due to land conversion from rice fields to housing, which increases surface runoff and flood risk. This research aims to design infiltration ponds to reduce storm water runoff. The calculation method of infiltration ponds is based on Indonesian National Standard 2398-2017 and the site test is based on Indonesian National Standard 8456:2017. The calculation results show the effectiveness of infiltration ponds in reducing runoff discharge, with the service area divided by four and then averaged and obtained the results of 16,590 (m³/h) runoff discharge, 16,590 (m³/h) applied discharge 100% effectiveness, with a total requirement of 15 infiltration well units.